Kemampuan pemecahan masalah matematis ditinjau dari motivasi belajar siswa sekolah dasar - Ilham Ali Robbani; Tina Sri Sumartini (Institut Pendidikan Indonesia, 2023)
This research is motivated by the results of other studies which show that mathematical problem-solving abilities are in line with students' learning motivation. The purpose of this study was to determine the increase in students' mathematical problem-solving abilities in terms of learning motivation. This study used a quantitative method with test instruments about problem solving abilities and student learning motivation questionnaires. As for the data processing by conducting instrument validity tests, normality tests, homogeneity tests, differentiating power tests and difficulty levels and finally conducting t tests or advanced tests. The population in this study were students at an elementary school in Garut Regency. Sampling was done by purposive sampling. Based on the results of the analysis, it was concluded that, increasing student motivation will affect the increase in students' mathematical problem-solving abilities. This research has implications for previous research that motivation influences students' mathematical problem-solving abilities. So, it is hoped that the teacher in the class is able to increase student learning motivation.Penelitian ini dilatarbelakangi oleh hasil-hasil penelitian lainnya yang menunjukkan bahwa kemampuan pemecahan masalah matematis sejalan dengan motivasi belajar siswa. Tujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan pemecahan masalah matematis siswa ditinjau dari motivasi belajar. Penelitian ini menggunakan metode kuantitatif dengan instrumen tes soal kemampuan pemecahan masalah dan angket motivasi belajar siswa. Adapun proses pengolahan data dengan melakukan uji validitas instrumen, uji normalitas, uji homogenitas, uji daya pembeda dan tingkat kesukaran serta yang terakhir melakukan uji t atau uji lanjut. Populasi dalam penelitian ini adalah siswa di salah satu SD di Kabupaten Garut. Pengambilan sampel dilakukan secara purposive sampling. Berdasarkan hasil analisis tersebut diperoleh kesimpulan bahwa, Semakin meningkat motivasi belajar siswa akan mempengaruhi peningkatan kemampuan pemecahan masalah matematis siswa. Penelitian ini berimplikasi pada penelitian sebelumnya bahwa motivasi mempengaruhi dari kemampuan pemecahan masalah matematis siswa. Sehingga diharapkan guru di kelas mampu meningkatkan motivasi belajar siswa.